Incorporating perceived risks and Hygien belief into intention to use E-Wallet in Malaysia - Yew, Lim Kim; Fei, Goh Chin; Kowang, Tan Owee; Wei, Zhang; Udang, Lester Naces (International Journal of Innovative Research and Scientific Studies, 2025)
E-wallets have become a popular payment method, widely used in many advanced countries. However, in Malaysia, efforts are still underway to develop the e-wallet market. This study focuses on users’ perceptions of subjective norm, risk, hand hygiene beliefs, perceived usefulness, perceived ease of use, and continuance intention to use e-wallets. One reason for studying this topic is the lack of literature on the influence of hand hygiene beliefs on technology use. Survey questionnaires were used to measure respondents' responses to six variables from a research model. A total of 306 Touch ’n Go e-wallet users in Malaysia participated in this study. The researcher employed the Statistical Package for Social Science (SPSS) and Smart-PLS (Partial Least Squares) to analyze the collected data. The results indicated that subjective norm and risk significantly influenced perceived usefulness and perceived ease of use, which in turn affected the intention to use e-wallets. Additionally, hand hygiene beliefs did not significantly influence perceived usefulness but had a significant impact on continuance intention to use e-wallets. The findings can benefit both users and companies, aiding in product innovation and development in emerging markets.